Code Switching and Code Mixing in Critical Eleven Novel by Ika Natassa - Octa Pratama Putra; Unpris Yastanti (Scope : Journal of English Language Teaching, 2018)
Code switching and code mixing are the strategy of adapting two languages in a speech. The objective of this research is to find the reason why the characters switch or mix their speaking. Revealing and classifying the kinds of code switching and code mixing are also the aim of this study. The writer chooses novel as the object of this study because the characters of this novel are bilingual who are able to speak more than one language. The type of this research is library research. Therefore, in conducting this journal, descriptive qualitative is used as the method of the analysis. The writer collects data by reading the novel, and marking them to make it easier to analyze. The result of this research points out that code mixing is frequently used by the character in the novel. The writer has collected about five kinds of code switching externally and ten kinds of code mixing. Further result, they are five kinds of internal code mixing, and five kinds of external code mixing, and the rest, there are five of external code switching. They tend to choose lexical items that are appropriate from the language where their repertoire is more comprehensive